Pulmonary functions and life quality assessment results two years after COVID-19 comparison with the sixth month results - Bardakci, Mustafa İlteriş; Ozturk, Esin Nagihan; Ozkarafakili, Müfide Arzu; Ozkurt, Hüseyin; Yanc, Uğur; Yıldız, Dilek Sevgi (The Journal of Infection in Developing Countries, 2023)
Introduction: We aimed to investigate the effects of COVID-19 on patients 24 months after severe COVID-19 pneumonia. Methodology: Fifty-four patients with severe COVID-19 pneumonia were evaluated on the 24th month after discharge from the hospital. Spirometry and short form of health-related quality of life scale (SF-36) were used. Chest computed tomography (chest-CT) was performed and the findings were grouped according to lung involvement. Results: Forced expiratory volume in 1 second (FEV1) % values of 19 patients (35.18%) and forced vital capacity (FVC) % values of 23 patients (42.54%) were found lower than expected on the 24th month. Physical function, energy-vitality, social functionality and general health parameters were found lower than normal on the SF-36 scale. 27 (50.00%) patients had a chest-CT abnormality. There was a correlation between FEV1% and FVC% values and group 3: medium-lower lobe dominant, reticulation + traction, 10-50% surface area. Chest-CT of 6 patients was fully recovered. No correlation was found between chest-CT findings on the 24th month and BMI, length of hospitalization, white blood cell (WBC), lymphocyte, C-reactive protein (CRP), ferritin and D-dimer values at the time of hospitalization. Conclusions: Functional and radiological abnormalities were detected in a significant number of patients on the 24th month. A systematic monitoring plan must be established to assess and properly manage the long-term problems that may arise.